Power, Trust, and Integrity: A Sociological Analysis of Corporate Size, Managerial Control, and Financial Transparency in Indonesia’s Energy Industry - Eneng Fitri Zakiyah; Taufik Akbar (Baileo: Jurnal Sosial Humaniora, 2026)
This study investigates the sociological dynamics shaping corporate financial integrity in Indonesia’s energy sector by analyzing how power, trust, and integrity interact within organizational governance structures. It examines the effects of firm size, managerial ownership, and leverage on financial reporting integrity, with audit quality serving as a moderating variable. Using a quantitative explanatory design with sociological interpretation, the study employs panel data regression and moderated regression analysis (MRA) on 49 energy firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The findings reveal that firm size has a significant negative effect on financial reporting integrity, reflecting the role of power asymmetry and structural complexity in large organizations. Conversely, managerial ownership shows a significant positive impact, indicating that managerial control fosters trust and accountability, while leverage exhibits no significant influence. Audit quality moderates these relationships by mitigating the negative impact of firm size and amplifying the positive influence of managerial ownership, but it does not affect leverage. The study’s novelty lies in integrating sociological theory into financial analysis, conceptualizing audit quality as a mechanism of social control that legitimizes managerial conduct and sustains institutional trust. This research contributes to the advancement of organizational sociology and governance studies by reframing financial transparency as a moral and institutional practice within corporate systems.